Level-k reasoning and time pressure in the 11-20 money request game - Florian Lindner; Matthias Sutter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
Arad and Rubinstein (2012a) have designed a novel game to study level-k reasoning experimentally. Just like them, we find that the depth of reasoning is very limited and clearly different from equilibrium play. We show that such behavior is even robust to repetitions, hence there is, at best, little learning. However, under time pressure, behavior is, perhaps coincidentally, closer to equilibrium play. We argue that time pressure evokes intuitive reasoning and reduces the focal attraction of choosing higher (and per se more profitable) numbers in the game.
Keywords: C91; C72; 330; Level-k reasoning; Time pressure; Repetition; Experiment; Nichtkooperatives Spiel; Test